Analysis Of Digital Marketing Strategies In Increasing Sales Of B21 Digital Printing In Gresik City - Fito Hanif Ramadhan; Fani Khoirotunnisa (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the digital marketing strategy implemented by B21 Digital Printing in Gresik City and its impact on increasing sales. With the rapid development of information and communication technology, the use of digital platforms in marketing products is very important for business actors, including B21 Digital Printing. This research uses a qualitative approach and type of field research. A planned digital marketing strategy can help companies understand audiences, create relevant content, utilize various digital channels, and analyze data to optimize marketing campaigns. Through this combination of strategies, B21 Digital Printing successfully utilizes digital technology to strengthen its position in the market, increase sales, and build closer relationships with consumers. The integration of data analytics enables continuous evaluation and adjustment of strategies to achieve more optimal results. With the implementation of the right digital marketing strategy, it can significantly contribute to the increase in sales of B21 Digital Printing in Gresik City.